Hopes and prospects [compact disc, unabridged] - Chomsky, Noam (Haymarket Books, 2011)
Argues that direct participation in action in the United States, Latin America, Bolivia, and Haiti has put into practice a different model of democracy that could portend more far-reaching, badly needed changes.